TECHNOLOGY AND ETHICS: Guardini’s Legacy in Laudato Sí - Rajcani, Jakub (Asian Horizons, 2016)
In this paper I argue that Pope Francis, as well as the author quoted by him — Romano Guardini, agree that technology is intrinsically a human dimension of life that is ambiguous. On the one hand, it has to be approved and used for higher goals, on the other is always to be evaluated and confronted with real and true values. Technology is destined to help nature but is radically based on, rooted in and dependent on it, as is the case of the relationship between nature and culture, and nature and grace. Humans must not let themselves be ruled by “impersonal forces.” Development — that not always is a true progress — will not be infinite.